Question
upstudy study bank question image url

Section 7.3 Practice: Prove each Identity. 1) \( \sec (x)-\sin (x) \tan (x)=\cos (x) \)

Ask by Wright Lynch. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

To prove the identity \( \sec(x) - \sin(x) \tan(x) = \cos(x) \), follow these steps: 1. **Rewrite Trigonometric Functions:** - \( \sec(x) = \frac{1}{\cos(x)} \) - \( \tan(x) = \frac{\sin(x)}{\cos(x)} \) 2. **Substitute into the Identity:** \[ \frac{1}{\cos(x)} - \sin(x) \cdot \frac{\sin(x)}{\cos(x)} = \frac{1 - \sin^2(x)}{\cos(x)} \] 3. **Apply Pythagorean Identity:** \[ 1 - \sin^2(x) = \cos^2(x) \] So, \[ \frac{\cos^2(x)}{\cos(x)} = \cos(x) \] 4. **Simplify:** \[ \cos(x) \] Thus, the identity is proven.

Solution

To prove the identity   sec(x) – sin(x)·tan(x) = cos(x), start by rewriting the trigonometric functions in terms of sine and cosine: • sec(x) = 1/cos(x) • tan(x) = sin(x)/cos(x) Now substitute these into the left-hand side of the identity:   sec(x) – sin(x)·tan(x)     = 1/cos(x) – sin(x)·(sin(x)/cos(x))     = 1/cos(x) – sin²(x)/cos(x) Since both terms have the common denominator cos(x), combine them:   = [1 – sin²(x)]/cos(x) Recall the Pythagorean identity:   sin²(x) + cos²(x) = 1  or  1 – sin²(x) = cos²(x) Substitute cos²(x) for 1 – sin²(x):   = cos²(x)/cos(x) Simplify by canceling one factor of cos(x):   = cos(x) Thus, we have shown:   sec(x) – sin(x)·tan(x) = cos(x) This completes the proof of the identity.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To prove the identity \( \sec (x) - \sin (x) \tan (x) = \cos (x) \), we can start by rewriting the left side using their definitions. We know that \( \sec(x) = \frac{1}{\cos(x)} \) and \( \tan(x) = \frac{\sin(x)}{\cos(x)} \). Therefore, the expression becomes: \[ \frac{1}{\cos(x)} - \sin(x) \cdot \frac{\sin(x)}{\cos(x)} = \frac{1}{\cos(x)} - \frac{\sin^2(x)}{\cos(x)} \] Combining the two fractions over a common denominator, we get: \[ \frac{1 - \sin^2(x)}{\cos(x)} \] Using the Pythagorean identity \( 1 - \sin^2(x) = \cos^2(x) \), we can substitute to simplify: \[ \frac{\cos^2(x)}{\cos(x)} = \cos(x) \] Thus, we’ve proven \( \sec(x) - \sin(x) \tan(x) = \cos(x) \). Now, let's remember that this identity is equal to a specific form of the relationship between sine, cosine, and secant functions, showcasing how they can transform into each other through simple manipulations. Understanding trigonometric identities can help you identify them in complex expressions, making problem-solving easier! When dealing with trigonometric functions, it’s crucial to keep fundamental identities handy for quick simplifications or proofs. Common mistakes often stem from misapplying the identities or neglecting to recognize equivalent forms. Always double-check your steps for clarity!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy